Students’ Perception Toward Implemetion of Peer, Self and Teacher Corrections on Students’ English Grammar Mastery at English Education Department Teacher Training and Education Faculty of UKI Toraja (Jurnal Keguruan dan Ilmu Pendidikan, 2019)
The objective of this reasearch are 1) To find out what are the positeive perception of the students of UKI Toraja toward Implemetion Of Peer, Self And Teacher Corrections On Students’ English Grammar Mastery. 2). To find out what are the negative perception of the students of UKI Toraja toward Implemetion Of Peer, Self And Teacher Corrections On Students’ English Grammar Mastery. The sample of this rsearch consist of 10 students was taken by using accidental sampling technique. The writer used semi interview to find the data of this rsearch. And the result of this research showed that there were some positive and negative toward implementation Peer, Self And Teacher Corrections On Students’ English Grammar Mastery At English Education Department Teacher Training. The positive perception are 1). improve students 'writing skills ,students have more role in correcting their peers' mistakes, students are better able to understand the explanations from their own friends, to realize students' writing skills. increasing students' knowledge2). The students can realize mistakes they made and they improve theirself automatically. 3) Make teachers understand student work and find errors in each student's assignments. the score of students is more real The teacher can know the extent to which the students can understand the material taught teachers or lecturers can be active , the teacher immediately correct the studuents work. Easier for teachers to find errors. However there were several negative perceptiton of this method are 1). The students some time cannot correct their work one another because they do not understand about the material they studied. 2). The teacher sometime do not correct the students’ paper carefully.